Pursuing Plurality: Exploring the Synergies and Challenges of Knowledge Co-production in Multifunctional Landscape Design - Chakraborty, Ritodhi; Jayathunga, Sadeepa; Matunga, Hirini Paerangi; Davis, Shannon; Matunga, Lizzie; Eggers, James; Gregorini, Pablo (Frontiers in Sustainable Food Systems, 2022)
Knowledge co-production has emerged as an important conceptual and processual tool in sustainability research addressing the needs of equity and inclusion. Indigenous communities and local people have engaged with the process of knowledge production, foregrounding their historical relationships with landscapes, based on their unique worldviews and knowledges. However, knowledge co-production, especially for multi-functional landscapes remains a contentious and complicated affair with enduring issues of power-sharing related to the different socio-political positions of stakeholders. This work explores the synergies and challenges in knowledge co-production for landscape re-design in the south Island of Aotearoa NZ through an assessment of the work done at the Centre for Excellence, Lincoln University. At this centre, a multi-stakeholder team is grappling with designing a farm, through a transdisciplinary framework that attempts to include multiple worldviews. This work explores the various stages of the co-production process, analysing the exchanges between various members as they prepare for co-production, the knowledge produced through this engagement, and how this knowledge is being utilised to further the goal of sustainability. Our results show that significant gaps remain between co-production theory and co-production practice which are a result of the mismanagement of the co-production process, the mismatch in the time and spatial scales of project goals, and the differences in the values and objectives of the different stakeholders. However, the process of co-production, though flawed, leads to the building of more open relationships between the stakeholders, and leads to some very meaningful knowledge products that address the multi-temporal and multi-spatial aspirations of multi-functional landscapes in Aotearoa NZ, while contributing to the broader scholarship on co-production in sustainability. Finally, both synergies and challenges prove meaningful when challenging the roadblocks to the inclusion of a diversity of worldviews, by clearly highlighting the places of engagement and why they were made possible. We suggest that knowledge co-production attempts in multi-functional landscapes around the world should attempt a similar assessment of their process. This can help build better relationships between scientists and IPLC, address disciplinary bias and marginalization of non-expert opinions, while also ensuring the relevance of the research to the multiple stakeholders of the land.